Alterations in metalloprotein abundance under ocean warming in the marine green alga Micromonas pusilla using the mebipred predictive tool - Dedman, CJ; Fournier, M; Rickaby, REM (Elsevier, 2024)
Metals are essential to life, required for the functioning of a substantial fraction of proteins. Marine phytoplankton drives the oceanic carbon cycle, influencing global biogeochemistry. These organisms rely on trace metal nutrients; however how trace nutrient demand will change under ocean warming is uncertain. The currently limited annotation of metalloproteins contributes to this lack of understanding. Herein, we utilise the recently published mebipred tool to predict the metalloproteome of the globally occurring green alga, Micromonas pusilla, revealing ∼20 % of its reference proteome to display ion-binding properties. Using the predicted metalloproteome, and existing Gene Ontology annotation, we present a comprehensive insight towards changes in metalloprotein abundance after exposure to ocean warming conditions (+6 °C), using a shotgun proteomic approach. We outline that predictions must be combined with existing annotation to fully capture the metalloprotein response. Approximately 50 % of identified metalloproteins significantly altered in abundance under warming, largely related to changes in cellular function. Notably, warming appeared to shift Fe use from photosynthesis to storage in M. pusilla, indicated by a 2.36 log2 fold-increase in ferritin and decline in abundance of photosynthetic proteins. Ocean warming will inevitably alter cellular use and demand for metal cofactors in marine phytoplankton with possible implications for biogeochemical cycling. Bioinformatics tools such as mebipred greatly expand our ability to examine such changes.